Observation and imitation of actions performed by humans, androids, and robots: an EMG study - Hofree, Galit; Urgen, Burcu A.; Winkielman, Piotr; Saygin, Ayse P. (Frontiers in Human Neuroscience, 2015)
Understanding others’ actions is essential for functioning in the physical and social world. In the past two decades research has shown that action perception involves the motor system, supporting theories that we understand others’ behavior via embodied motor simulation. Recently, action perception has been facilitated by using well-controlled artificial stimuli, such as robots. One key question this approach enables is what aspects of similarity between the observer and the observed agent facilitate motor simulation? Since humans have evolved among other humans and animals, using artificial stimuli such as robots allows us to probe whether our social perceptual systems are tuned to process other biological entities. In this study, we used humanoid robots with different degrees of humanlikeness in appearance and motion along with electromyography (EMG) to measure muscle activity in participants’ arms while they either observed or imitated videos of three agents produce actions with their right arm. The agents were a Human (biological appearance and motion), a Robot (mechanical appearance and motion) and an Android (biological appearance, mechanical motion). Right arm muscle activity increased when participants imitated all agents. Increased muscle activation was found also in the stationary arm both during imitation and observation. Furthermore, muscle activity was sensitive to motion dynamics: activity was significantly stronger for imitation of the human than both mechanical agents. There was also a relationship between the dynamics of the muscle activity and motion dynamics in stimuli. Overall our data indicate that motor simulation is not limited to observation and imitation of agents with a biological appearance, but is also found for robots. However we also found sensitivity to human motion in the EMG responses. Combining data from multiple methods allows us to obtain a more complete picture of action understanding and the underlying neural computations.